2019
DOI: 10.3390/ma12020297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Deposition on Powder Bed and Specimen Properties

Abstract: Three-dimensional printing used to be a rapid prototyping process, but nowadays it is establishing as an additive manufacturing (AM) process. One of these AM techniques is selective laser sintering (SLS), which most often involves partial melting of the particles and therefore belongs to the category of powder bed fusion processes. Much progress has been made in this field by research on process parameters like laser power, hatch distance, and scanning speed while still lacking a fundamental understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…PBF-LB is a layer-by-layer powder processing technique, and in each layer, the recoater spreads powder feedstocks on the building platform. During spreading, powder feedstocks must have excellent flowability to increase powder bed density and facilitate recoating a homogeneous and defect-free powder layer [74]. Since there is no international standard to measure PBF-LB powder feedstocks' flowability, a combination of several techniques such as density measurement (Hausner ratio, HR), ring shear test, and the rotating drum has to be used to measure the unmodified and additivated powder feedstocks' flowability.…”
Section: Flowabilitymentioning
confidence: 99%
“…PBF-LB is a layer-by-layer powder processing technique, and in each layer, the recoater spreads powder feedstocks on the building platform. During spreading, powder feedstocks must have excellent flowability to increase powder bed density and facilitate recoating a homogeneous and defect-free powder layer [74]. Since there is no international standard to measure PBF-LB powder feedstocks' flowability, a combination of several techniques such as density measurement (Hausner ratio, HR), ring shear test, and the rotating drum has to be used to measure the unmodified and additivated powder feedstocks' flowability.…”
Section: Flowabilitymentioning
confidence: 99%
“…Although the materials manufactured by FDM showed the most anisotropic levels, few researchers reported some noticeable levels of mechanical anisotropy in parts printed by SLS [ 13 , 18 , 19 , 20 ]. For instance, Ajoku et al reported the use of polyamide 12 (PA12) in producing parts with selected laser sintering (SLS).…”
Section: Materials Anisotropy In Additively Manufactured Polymer Partsmentioning
confidence: 99%
“…Their samples showed a discrepancy of 16 per cent in tensile strength and 11.2 per cent in modulus for parts printed in the X, Y, and Z axes leading to unequal and lower mechanical properties in parts printed in Z build orientation than X orientation [ 18 ]. Beitz et al also reported a 48.6 per cent difference when build orientation was altered [ 19 ]. On the other hand, some other researchers reported no significant changes in the tensile strength of the parts printed by SLS [ 21 ].…”
Section: Materials Anisotropy In Additively Manufactured Polymer Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the spreading and compression of the powder have an important effect on the properties of the printed parts. Beitz et al [47] offered an interesting summary of the results obtained by different authors on the spreading and compression of powder beds with different devices. They concluded, through the study of the spreading of nylon PA12 powders, that an even compression of the powder bed is better achieved when using both, a scraper or blade and a counter-rotating roller.…”
Section: Powder Compressionmentioning
confidence: 99%